Studi Pada Kantor Otoritas Pelabuhan Utama Tanjung Perak - Dian Arisanti; Noer Rohmah Diah A’yuni; Soedarmanto (Fakultas Ekonomi Universitas Yos Soedarso, 2024)
The research is a study at the Tanjung Perak Main Port Authority Office, Surabaya. And this research also aims to analyze the factors that have the most dominant influence on employee performance. This research is a type of quantitative research, which consists of four variables, namely Occupational Safety and Health (K3) (X1), Work Environment (X2), Work Discipline (X3), and Employee Performance (Y). This research used a sample of 75 employees of the Tanjung Perak Main Port Authority Office, Surabaya. This research uses data collection methods in the form of interviews, observations, questionnaires. The data analysis method used is descriptive analysis, data quality test, classical assumption test, t test using SPSS calculations. The results of the analysis state that: (1) the t-count result is 0.653 < 1.996 t table so Occupational Safety and Health (K3) does not have a positive and significant effect on Employee Performance, (2) the t count result is 2.776> 1.994 t table so the Work Environment has a positive and significant effect on Employee Performance, (3) tcount results 5,235 > 1,994 ttable Physical Work Discipline has a positive and significant effect on Employee Performance. The results of this research show that K3, Work Environment.